An integrated population model sheds light on the complex population dynamics of a unique colonial breeder. Issue 4 (19th June 2019) - Jansen, Dorine Y. M.; Pradel, Roger; Mares, Rafael; Doutrelant, Claire; Spottiswoode, Claire N.; Covas, Rita; Altwegg, Res
Abstract: Climate models forecast increasing climatic variation and more extreme events, which could increase the variability in animal demographic rates. More variable demographic rates generally lead to lower population growth and can be detrimental to wild populations, especially if the particular demographic rates affected are those to which population growth is most sensitive. We investigated the population dynamics of a metapopulation of 25 colonies of a semi‐arid bird species, the sociable weaver Philetairus socius, and how it was influenced by seasonal weather during 1993–2014. We constructed an integrated population model which estimated population sizes similar to observed population counts, and allowed us to estimate annual fecundity and recruitment. Variance in fecundity contributed most to variance in population growth, which showed no trend over time. No weather variables explained overall demographic variation at the population level. However, a separate analysis of the largest colony showed a clear decline with a high extinction probability (0.05 to 0.33) within 5 years after the study period. In this colony, juvenile survival was lower when summers were hot, and adult survival was lower when winters were cold. Rainfall was also negatively correlated with adult survival. These weather effects could be due to increased physiological demands of thermoregulation and rainfall‐induced breeding activity. Our results suggest that the dynamics of the population on the whole are buffered against current weather variation, as individual colonies apparently react in different ways. However, if more and increasingly extreme weather events synchronize colony dynamics, they are likely to have negative effects. Abstract : Large areas of the globe are arid, yet population dynamics of arid zone birds is poorly understood. We developed an integrated population model to study population dynamics of the sociable weaver, a keystone species in southern Africa's arid areas. Reproduction was most closely associated with variation in population size, confirming the importance of this demographic rate in an arid zone bird where reproduction is strongly dependent on rainfall.